Pharmaceutical patents: incentives for R&D or marketing? - Kurt R. Brekke; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2008)
We analyse how a patent-holding pharmaceutical firm may strategically use advertising of existing drugs to affect R&D investments in new (differentiated) drugs, and thereby affect the probability distribution of future market structures in the industry. Within a fairly general model framework, we derive exact conditions for advertising and R&D being substitute strategies for the incumbent firm and show that it may overinvest in advertising to reduce the incentive for an entrant to invest in R&D, thereby reducing the probability of a new product on the market. In a more specific setting of informative advertising, we show that such overinvestment incentives are always present, and that more generous patent protection implies that a larger share of the patent rent is spent on marketing, relative to R&D.
Keywords: I11; L13; O31; 330; Marketing; Research & Development; pharmaceutical; Pharmazeutisches Produkt; Patent; Industrielle Forschung; Marketing; Strategische Unternehmensplanung; Betriebliche Investitionspolitik; Marktstruktur; Dynamisches Spiel